Perilaku Konsumtif Mahasiswa Dalam Membeli Produk Fashion Di Universitas PGRI Wiranegara Pasuruan - Nanda Eka Amilia (Pusat Riset dan Inovasi Nasional, 2025)
This article aims to analyze the factors that influence the consumer behavior of PGRI Wiranegara Pasuruan University students in purchasing fashion products. The approach used in this article is a qualitative approach, and data collection for this article is interviews and closed questionnaires with 10 PGRI Wiranegara Pasuruan University students. The results of this research show that peers and family can be the biggest motivating factors in carrying out excessive consumptive behavior. This research contributes to the understanding of student consumer behavior.